Pengaruh Reward dan Punishment dalam Teori Behaviorisme Terhadap Partisipasi Siswa di Kelas II SD Inpres 1 Tondo - Sindi Mayastri Buru; Sukri; Deliani Pratiwi; Mohamad Fadil (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2026)
Student participation in the learning process is one of the important indicators in determining the success of learning in elementary schools. Low student participation can hinder the achievement of learning objectives optimally; therefore, appropriate strategies are needed to increase student involvement. One approach that can be applied is the implementation of reward and punishment based on behaviorism theory. This study aims to analyze the effect of reward and punishment on student participation in Grade II at SD Inpres 1 Tondo. This research used a descriptive method with a qualitative approach. Data collection techniques were carried out through questionnaires and documentation, while data analysis used percentage calculations to determine the tendency of student responses. The results showed that rewards received a positive response of 80%, which is categorized as very good, while punishment obtained a percentage of 55%, which is categorized as fairly good. This indicates that rewards have a more dominant influence in increasing student participation compared to punishment. Thus, the proper and proportional implementation of reward and punishment can improve students’ motivation and activeness in learning activities.